2000
DOI: 10.1016/s0168-9452(00)00270-3
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of UDP-glucose: hydroxycoumarin 7-O-glucosyltransferase, with broad substrate specificity from tobacco cultured cells

Abstract: The enzyme UDP-glucose: hydroxycoumarin 7-O-glucosyltransferase (CGTase), which catalyzes the formation of scopolin from scopoletin, was purified approximately 1,200-fold from a culture of 2,4-D-treated tobacco cells (Nicotiana tabacum L. cv. Bright Yellow T-13) with a yield of 7%.Purification to apparent homogeneity, as judged by SDS-PAGE, was achieved by sequential anion-exchange chromatography, hydroxyapatite chromatography, gel filtration, a second round of anion-exchange chromatography, and affinity chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
40
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 32 publications
3
40
1
Order By: Relevance
“…The samples for enzyme assay were extracted from the residual cells with Tris-HCl (pH 7.5) containing 5 mM β-mercaptoethanol as described [28]. GTase reactions were performed for 60min at 30 ºC using 200 µM 1-or 2-naphthol and 500 µM UDP-glucose as substrates, then the generated glucoside was determined by HPLC.…”
Section: Metabolism Of Naphthols In the Tobacco Cellmentioning
confidence: 99%
“…The samples for enzyme assay were extracted from the residual cells with Tris-HCl (pH 7.5) containing 5 mM β-mercaptoethanol as described [28]. GTase reactions were performed for 60min at 30 ºC using 200 µM 1-or 2-naphthol and 500 µM UDP-glucose as substrates, then the generated glucoside was determined by HPLC.…”
Section: Metabolism Of Naphthols In the Tobacco Cellmentioning
confidence: 99%
“…Moreover, several GTase genes have been reported, namely, genes of IEGT, TOGT, jasmonate-inducible GTase gene (JIGT) [19], and salicylic acid GTase gene [20]. In our previous studies, the glucosylation activity in cultured tobacco cells was investigated [21][22][23]. We isolated GTase genes (NtGT1a, NtGT1b and NtGT3) whose encoding enzymes have glucosylation activity against many kinds of phenolics, such as flavonoids, coumarins and naphthols [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…1A). As one of the major antioxidants derived from plant sources, quercetin is beneficial to human health and has been ascribed anticancer (20 -22), anti-inflammatory (23,24), and anti-allergic activity (25,26). In nature quercetin is often glycosylated on one or more of the five hydroxyl groups to increase its solubility, stability, and bioavailability.…”
mentioning
confidence: 99%
“…Recent studies have suggested that many plant secondary metabolite UGTs are more regiospecific than substrate specific (11,(22)(23)(24)(25)(26). Recently, UGTs from Arabidopsis thaliana were extensively analyzed both in vitro and in vivo with quercetin as acceptor; from a total of 29 UGTs that exhibited activity with quercetin, 14 catalyzed glycosylation either on the C-ring 3-hydroxyl or the A-ring 7-hydroxyl, the most commonly reported glycosylation positions for quercetin derivatives isolated from plants.…”
mentioning
confidence: 99%